2022
DOI: 10.3390/ijerph19053027
|View full text |Cite
|
Sign up to set email alerts
|

Drag Effect of Economic Growth and Its Spatial Differences under the Constraints of Resources and Environment: Empirical Findings from China’s Yellow River Basin

Abstract: As the global economic development intensifies the plunder of resources and the environment, the constraints are becoming more and more obvious. Based on the background of the strategy for ecological conservation and high-quality development of the Yellow River Basin, this paper intends to construct a resource-environment-constrained economic growth drag effect model and a spatial Dubin model, and explore the economic growth drag effect and its spatial differences in the Yellow River Basin under the constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As the transformation of the energy structure in the Yellow River Basin is the focus of the "double carbon" target, the existing studies related to this region mainly focus on analysis of the factors influencing carbon emissions under the "double carbon" target [25,26], analysis of the factors influencing green development [27][28][29], and analysis of the coupling between economic growth and carbon neutrality [30,31]. The studies directly related to energy, analyze the impact of the carbon footprint for energy consumption [32] and the coupling and coordination of the system as a whole on regional sustainable development [33][34][35][36], etc.…”
Section: Literature Review 21 Energy Transition Studiesmentioning
confidence: 99%
“…As the transformation of the energy structure in the Yellow River Basin is the focus of the "double carbon" target, the existing studies related to this region mainly focus on analysis of the factors influencing carbon emissions under the "double carbon" target [25,26], analysis of the factors influencing green development [27][28][29], and analysis of the coupling between economic growth and carbon neutrality [30,31]. The studies directly related to energy, analyze the impact of the carbon footprint for energy consumption [32] and the coupling and coordination of the system as a whole on regional sustainable development [33][34][35][36], etc.…”
Section: Literature Review 21 Energy Transition Studiesmentioning
confidence: 99%
“…And as a consequence, GDP growth is hampered under the energy constraints. "Growth drag effects model" is another popular tool to describe the impacts of energy and resources constraints on economic growth (Zhao et al, 2019;Zhang et al, 2022;Zhou et al, 2022). It has first been introduced to explore the impacts of limited ecological factors input on economic issues by Nordhaus (1992).…”
Section: Open Access Edited By 1 Introductionmentioning
confidence: 99%
“…An et al (2018) quantitatively analyzed the constraint effect of water consumption on the urbanization of the Yangtze River Economic Belt, and stated that the urbanization process of the Yangtze River Economic Belt has slowed down by 0.574%, due to the constraints of water resources consumption. Zhou et al (2022) reported that the total drag effect of natural resources on economic growth in the Yellow River Basin is about −0.8347 through the classic panel model estimation. Pan et al (2021) found that the drag growth effect of water resources in Chongqing was about 0.3%-0.5%, slightly less than the result of Chengdu, which reflected the relatively lower dependence of industrial development in Chongqing on water resources.…”
Section: Open Access Edited By 1 Introductionmentioning
confidence: 99%
“…Is air pollution detrimental to regional innovation? An empirical heterogeneity test based on Chinese cities Introduction With economic globalization and extensive economic growth in recent years, the global ecological environment is deteriorating day by day, which poses a challenge to the sustainable development of the world's economy and environment (1). Due to the extensive economic growth, the consumption of resources and energy has increased (2), the level of biodiversity has decreased, and the contradiction between human habitat activity and ecological environment has become increasingly prominent (3).…”
mentioning
confidence: 99%